Dynamics of Implementing the New MABIMS Criteria on the Hijri Calendar (Takwīm Hijri) By the Indonesian and Malaysian Governments - Mulyadi, Achmad; Mamah, Siti Musawwamah; Hosen, Hosen; Saiful, Mohd. Saiful Anwar (Universitas Islam Negeri Raden Intan Lampung, 2025)
The Islamic calendar unification effort has long been undertaken by MABIMS (Ministries of Religious Affairs of Brunei Darussalam, Indonesia, Malaysia, and Singapore) through new criteria approved in 2019: a minimum crescent height of 3° and a minimum elongation of 6.4°. Since 2021, Indonesia and Malaysia have both adopted these criteria in their respective Islamic calendars, although the implementation stages differ between the two countries. This is due to challenges, particularly related to weather conditions, crescent observation technology, and human resource capacity. This paper aims to explore regulatory policies related to the implementation of the new MABIMS criteria, including analyzing the dynamics of their implementation. Data were collected and analyzed qualitatively using a deductive-inductive thinking model and a phenomenological approach. This study found that Indonesia and Malaysia have shown a strong commitment to implementing the MABIMS criteria in their respective Hijri calendars. Still, the Indonesian Government establishes a policy for the beginning of the Hijri month with a moderation paradigm because it must involve mass organizations and local wisdom values. In contrast, the Malaysian Government establishes a policy centrally, uniformly and institutionally through the JAKIM authority. In addition, the Indonesian Government integrates the hisāb and rukyat methods in a decentralized manner so that sometimes there are differences in determining the beginning of the month of Ramadan, Shawwal and Dzulhijjah in the Community. While the Malaysian Government applies it centrally, uniformly and applies to all states. In addition, Indonesian Muslim citizens accept the Government's determination, although with differences in determining the date, while Malaysian Muslims accept the Government's determination simultaneously and uniformly across all states